Sosialisasi Peraturan Daerah Kota Pariaman Nomor 20 Tahun 2012 Tentang Jaminan Kesehatan Sabiduak- Sadayuang (JK-SS) Dalam Rangka Memberikan Jaminan Kesehatan Masyarakat Di Kecamatan Pariaman Tengah, Kota Pariaman - Delfina Gusman; Arfiani Arfiani; Henny Andriani; Alsyam Alsyam; Charles Simabura (Jurnal Pengabdian Warta Andalas, 2016)
Applicable local Pariaman Number 20 in 2012 About Providence health coverage Sabiduak Sadayuang (JK-SS) was established by the Government of Pariaman as a policy area in order to improve the policies of the Central Government to enact public health assurance program. Regulation of this area aims to ensure the public health Pariaman thoroughly. Health coverage in this area is not only intended for poor communities in Pariaman, but also intended for the children of Pariaman. In the provisions of article 5 paragraph (1) of the Regulation region of Pariaman number 12 in 2012 says that the audience is any person and or family members of citizens of the city of Pariaman who have paid dues or contributions.